On the health scene - Lambing, Mary Lou.; King, Mary Frances, 1925-. (New York: Springer Pub., 1976)
Discusses health care in the United States today including its shortcomings and its potential and describes the wide variety of careers available in the health field.
Bibliography: p. 157-159.
Keywords: Medicine -- Vocational guidance; Medical care -- United States